Factors Relating To The Role Of The Husband In Preparation For Birth In 3rd Trimester Pregnant Women In The Working Area Of The UPT Puskesmas Tabukan - Dyas, Sri Wahyuning; Maolinda, Winda; Ulfa, Ika Mardiatul (SEAN Institute, 2024)
Emotional support can provide husbands during labor continuously. Mothers who receive emotional support during labor will experience shorter labor times, fewer medical interventions and better birth outcomes. The husband's presence in childbirth provides at least three roles in the mother's birth process. The first role is as a trainer, a husband accompanies and helps the mother during and after labor contractions. This article aims to identify factors related to the role of husbands in preparing for delivery of third trimester pregnant women in the working area of ​​the UPT Puskesmas Tabukan. The approach used in this research is quantitative with the Cross Sectional method and the sampling technique is total sampling. The sample in this study amounted to 36 people. The data collection technique in this research used a questionnaire and was analyzed using the chi square test. Based on cross tabulation analysis, it shows that the husband's role in knowledge is 9 people's low, 9 people's knowledge is high and the husband's role is 18 people's. The husband's role was less in the negative attitudes of 8 people, and in the positive attitudes of 28 people. The husband's role in supporting the husband does not support 5 people, and the husband's support supports 30 people. Based on the results of the research: 25% of the husband's role is low, 25% of the husband's role is medium and 50% of the husband's role is high, 83.3% of the husband's knowledge is high and 16.7% of the husband's knowledge is low, 77.8% of the husband's attitude is positive and 22.2% of the husband's negative attitude is %. Husband's support supports 86.1% and husband's support does not support 13.9%.